Dreams and dream reports in the writings of Josephus : a traditio-historical analysis - Gnuse, Robert Karl, 1947- (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1996)
This volume analyzes the understanding of dreams and the corresponding literary forms used by Josephus in his writings. Josephus reports dreams as either auditory message dreams, symbolic visual dreams, or dream image appearances. In this regard he uses the format for auditory and visual dreams found in ancient Near Eastern and biblical texts, while his dream image appearance reports show familiarity with traditional Greek modes of reporting dreams. Close attention is given to the following topics: 1) the development of dream reports in the ancient Near East, the Bible, and the Hellenistic world; 2) Josephus' views on dreams and prophecy; 3) a form-critical assessment of Josephus' dream reports; and 4) an evaluation of Josephan dream reports which exhibit a more complex traditio-historical development.